Affective Evictions: - Anna Meera Gaonkar (Kvinder, Køn & Forskning)
The article suggests that government statements on anti-ghetto (2021) and security (2020) initiatives feature expressions of ‘white homesickness’ that manifest as longings for a national past and future with less or no migration to Denmark from outside Europe. The analysed statements justify the planned evictions of racialised-migrantised residents of social housing areas. The article argues that the statements also perform ‘affective evictions’ of racialised-migrantised members of society from the community of the imagined national home. Drawing on critical postmigration studies and a media-analytical approach to affect theory, two instrumentalised figures are accentuated as the haunting specters of this homesick politics: the fi gure of insecurity-creating immigrant boys and the figure of parallel societies inhabited by a ‘brown underclass.’ The article concludes that for racialised-migrantised residents of social housing estates in particular, the threat of ‘affective eviction’ paradoxically involves the material threat of eviction from society’s overarching welfare shelter, that is the threat of being deprived of the right to social security.